Farmers’ Knowledge on Soybean Production Technologies in Madhya Pradesh - Rajan, Parvez; Nahatkar, S. B.; Thomas, Moni (Indian Journal of Extension Education, 2021)
Soybean has emerged as a potential oilseed crop and has brought perceptible change in the economy of the farmers in the state of Madhya Pradesh. Demonstration on soybean production technologies were conducted under Technical Cooperation Project of Japan International Cooperation Agency (JICA). For present investigation primary data were collected from six beneficiaries and six non-beneficiaries soybean growers from six demonstration sites, the overall sample size comprises of 72 soybean growers (36 beneficiaries and 36 non-beneficiaries). The results showed that the knowledge level about soybean production technologies of beneficiary farmers was higher as compared to non-beneficiaries farmers and this was significantly associated with level of education whereas other socio-economic aspects were not associated with knowledge level about soybean production technologies.
Keywords: Knowledge level; Beneficiary & non beneficiary and soybean production technologies